Experimental and theoretical study on an intracavity KTiOPO4 optical parametric oscillator pumped by a dual loss modulated Q-switched and mode-locked laser. (1st July 2017) - Qiao, Junpeng; Zhao, Shengzhi; Yang, Kejian; Zhao, Jia; Li, Guiqiu; Li, Dechun; Li, Tao; Qiao, Wenchao; Chu, Hongwei; Luan, Chao
Abstract: In this paper, a sub-nanosecond KTiOPO4 (KTP)-based intracavity optical parametric oscillator (IOPO) pumped by a dual-loss modulated Q-switched and mode-locked (QML) laser with an acousto-optic modulator (AOM) and a Cr 4+ :YAG saturable absorber (Cr 4+ :YAG-SA) has been demonstrated. By changing the initial transmission of Cr 4+ :YAG-SA and the transmission of the output coupler at the signal wavelength, the signal pulse width compression can be realized. At an incident pump power of 8.3 W and an AOM repetition rate of 15 kHz, a single signal pulse underneath Q-switched envelope with the shortest pulse width of 220 ps was obtained. The experimental results reveal that this is a simple and effective way to obtain the sub-nanosecond OPO signal pulses. In addition, the related coupled rate equations have been set up and the simulation results agreed with the experimental results well. Highlights: A sub-nanosecond OPO pumped by a dual-loss modulated laser have been demonstrated. Signal pulse width can be compressed by selecting proper Cr 4+ :YAG and output mirrors. The simulation results agreed with the experimental results well.